1997
DOI: 10.1103/physrevlett.78.3165
|View full text |Cite
|
Sign up to set email alerts
|

HgSe: Metal or Semiconductor?

Abstract: From magnetotransport measurements it is generally believed that Hg-VI compounds show zero gap semiconducting behavior. Applying combined angle-resolved photoemission and inverse photoemission spectroscopy on HgSe(001) c͑2 3 2͒, we observe a positive fundamental gap of about 0.42 eV and a surface related state close to the Fermi level above the conduction band minimum. Following the results of this direct determination of the k-resolved band structure, previous experiments favoring zero gap models of Hg-VI com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…Photoelectron spectroscopic experiments carried out by Gawlik et al 4 on n-type HgSe indicated that this material should have a positive band gap of 0.42 eV. Later experiments, including the photoemission study by Janowitz et al 5 could not verify this, and it was concluded that HgSe is a semimetal.…”
Section: Introductionmentioning
confidence: 97%
“…Photoelectron spectroscopic experiments carried out by Gawlik et al 4 on n-type HgSe indicated that this material should have a positive band gap of 0.42 eV. Later experiments, including the photoemission study by Janowitz et al 5 could not verify this, and it was concluded that HgSe is a semimetal.…”
Section: Introductionmentioning
confidence: 97%
“…An exclusive group with these properties is known as semimetal or zero-gap semiconductors group (Delin and Kluner, 2002). Due to peculiar properties of mercury chalcogenides, many theoretical and experimental investigations have been undertaken which mainly include electronic-structure calculations (Rohlfing and Louie, 1998;Orlowski et al, 2000;Delin and Kluner, 2002;Delin, 2002;Fleszar and Hanke, 2005;Moon and Wei, 2006), photoemission spectroscopy (Gawlik et al, 1997), magneto-optical Fourier transform spectroscopy (von TruchseX et al, 2000), some optical properties (Markowski and Podgorny, 1992), etc.…”
Section: Introductionmentioning
confidence: 99%
“…HgS in the structure of zinc-blende (ZB) is used to produce nanocrystals or thin films [2]. Topological insulators, optoelectronic and spintronic applications, photovoltaic/photoconductive devices IR detectors and emitters, ohmic contact and removing mercury from exhaust gases, are some examples of their technological applications of mercury chalcogenides [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%